UBAYDULLAH KHAN'S MILITARY CAMPAIGNS TO KHORASAN: HISTORICAL SOURCES AND THEIR ANALYSIS - Farrux Fayzullayev (Modern American Journals, 2025)
This article analyzes the military campaigns of Ubaydullah Khan - one of the prominent representatives of the shaybanid dynasty - into Khorasan and their political significance. These campaigns constituted an important stage in the struggle between the shaybanids and the safavids during the 16th century. The analysis is based on historical sources and holds great importance for understanding the political and military processes of that period.
Keywords: Ubaydullah Khan, Khorasan, Herat, shaybanids, safavids, siege, battle, army, source, history.